Frontline to farm: Sustainable farming training for military veterans and beginning farmers - A.C. Fanatico; L.G. Gibbard; S.B. Bramall (Poultry Science)
New farmers are needed in agriculture in the U.S. to assure the sustainability of our food, including small- and mid-scale farmers. At the same time, military veterans need career opportunities as they transition back to civilian life. Many want to reconnect to community and the land. Training in sustainable agriculture and access to resources are needed for beginning farmers. Frontline to Farm is a new program at Appalachian State University in western N.C. to train military veterans in farming. We use a national/regional/community approach with on-line modules, as well as in-person training options. Specifically, 1) We have developed educational materials on-line with partners, the University of Arkansas and also the National Center for Appropriate Technology. These materials focus on sustainable farming, poultry, livestock, and pasture, as well as farm entrepreneurship and legal issues. 2) We also provide scholarships for veterans to attend sustainable agriculture conferences and training in the Southeast region. The University of Missouri offers training each summer on agroforestry, a regenerative agriculture practice that sequesters carbon while building soil fertility. 3) We provide intensive in-person trainings in our community in Southern Appalachia. We work closely with cooperative extension, USDA agencies, and local farmers for trainings. Several farmer veterans host customized internships at their farms to provide immersive experiences. 4) We provide our alumni with on-going consulting opportunities. We work with local farmer veteran mentors as consultants. Many farmers learn well in farmer-to-farmer settings. We leverage strengths in our community and work with local partners including Blue Ridge Women in Agriculture. We also work with local groups that support veterans, including Farmer Veteran Coalition and NC AgrAbility. Results in our first 3 years indicate that we have reached over 60,000 farmers electronically and over 220 in-person. Our project provides pathways to success (environmental, social, and economic) for new farmers. Sustainable agriculture protects environmental resources, increases equity for military veterans and beginning farmers, and builds resilience in local and regional food systems.